Implementation of Biosecurity Practices in Small Scale Layer Farms: Evidence from East Kalimantan, Indonesia - Indana, Khoiru; Ikhsan, M. Nur; Aprylasari, Dede; Adiputra, Kirana Dara Dinanti (CV. Komunitas Dunia Peternakan, 2025)
Biosecurity is a key concept in maintaining livestock health, directly influencing productivity by minimizing the risks of infectious and non-infectious diseases. This study aimed to assess the implementation level of the three biosecurity components conceptual, structural, and operational on layer chicken farms and their surrounding environment in Sangatta, East Kutai Regency. The research was conducted from December 2022 to February 2023 using purposive sampling, with criteria including a minimum population of 1,000 chickens, at least two years of operation, a basic understanding of biosecurity, and being in the productive phase. Data were collected through interviews and questionnaires based on a Likert scale to evaluate farmers’ responses. A total of 10 farmers participated in this study. The results showed that the overall implementation of biosecurity reached 49.6%, categorized as moderate. Meanwhile, 27.6% of respondents demonstrated a low level of understanding of biosecurity, which was higher than those with good understanding (22.6%). These findings indicate that biosecurity practices among layer chicken farmers in Sangatta are moderately applied, but awareness and comprehension still need to be improved.